Meningkatkan Kemampuan Motorik Halus Anak Usia Dini Melalui Kegiatan Meronce Pada Siswa Kelompok B di TK Nurul Huda Macanputih - Siti Sulasiyah; Andi Wapa (Jurnal Bintang Pendidikan Indonesia, 2024)
This research aims to improve the results of fine motor skills which previously at Nurul Huda Kindergarten there was still a lack of learning outcomes that emphasized fine motor skills. This research uses classroom action research to collect data from pre-cycle activities, cycle I and cycle II with the results obtained showing that students in the initial stage still do not meet the standards while the results of this research show that in cycle II, the research objectives were achieved, and in the second cycle stopped because the average student score from 2.3 to 3.4 and learning mastery also increased from 2.3% to 3.4%. Based on the data presented, it can be concluded that ronce activities can increase from the undeveloped category to very well developed.